Clinical Characteristics Associated with Return Visits to the Emergency Department after COVID-19 Diagnosis - Iltifat Husain (eScholarship Publishing, University of California, 2021)
Introduction: Patients diagnosed with coronavirus disease 2019 (COVID-19) require significant healthcare resources. While published research has shown clinical characteristics associated with severe illness from COVID-19, there is limited data focused on the emergency department (ED) discharge population. Methods: We performed a retrospective chart review of all ED-discharged patients from Wake Forest Baptist Health and Wake Forest Baptist Health Davie Medical Center between April 25–August 9, 2020, who tested positive for severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) from a nasopharyngeal swab using real-time reverse transcription polymerase chain reaction (rRT-PCR) tests. We compared the clinical characteristics of patients who were discharged and had return visits within 30 days to those patients who did not return to the ED within 30 days. Results: Our study included 235 adult patients who had an ED-performed SARS-CoV-2 rRT-PCR positive test and were subsequently discharged on their first ED visit. Of these patients, 57 (24.3%) had return visits to the ED within 30 days for symptoms related to COVID-19. Of these 57 patients, on return ED visits 27 were admitted to the hospital and 30 were not admitted. Of the 235 adult patients who were discharged, 11.5% (27) eventually required admission for COVID-19-related symptoms. With 24.3% patients having a return ED visit after a positive SARS-CoV-2 test and 11.5% requiring eventual admission, it is important to understand clinical characteristics associated with return ED visits. We performed multivariate logistic regression analysis of the clinical characteristics with independent association resulting in a return ED visit, which demonstrated the following: diabetes (odds ratio [OR] 2.990, 95% confidence interval [CI, 1.21–7.40, P = 0.0179); transaminitis (OR 8.973, 95% CI, 2.65–30.33, P = 0.004); increased pulse at triage (OR 1.04, 95% CI, 1.02–1.07, P = 0.0002); and myalgia (OR 4.43, 95% CI, 2.03–9.66, P = 0.0002). Conclusion: As EDs across the country continue to treat COVID-19 patients, it is important to understand the clinical factors associated with ED return visits related to SARS-CoV-2 infection. We identified key clinical characteristics associated with return ED visits for patients initially diagnosed with SARS-CoV-2 infection: diabetes mellitus; increased pulse at triage; transaminitis; and complaint of myalgias.